A sustainable and efficient recycling strategy of feather waste into keratin peptides with antimicrobial activity. (1st May 2022) - Qin, Xiaojie; Xu, Xiong; Guo, Yujie; Shen, Qingshan; Liu, Jiqian; Yang, Chuan; Scott, Elinor; Bitter, Harry; Zhang, Chunhui
Graphical abstract: Highlights: ICSE process at 1.5 MPa-120 s moderately destructed chicken feather (CF) without over-degradation. CF keratinolysis product showed anti- E.coli activity other than that from common proteolysis. CF keratinolysis product < 3 kDa had highest anti- E.coli activity with a high hydrophobic ratio. ICSE-keratinolysis was efficient for valorizing CF waste as antimicrobial product. Abstract: The study aimed to propose an efficient and eco-friendly strategy to improve the utilization of feather waste and converting it into high-valued antimicrobial products. Under the synergistic effect of instant catapult steam explosion (ICSE) (1.5 MPa-120 s), over 90% of chicken feather powder (CFP) was degraded into soluble peptides via keratinolysis within 3 h, about 90% of which were smaller than 3 kDa, indicating an overwhelming advantage than general proteolysis. Importantly, the keratinolysis hydrolysate of CFP was able to inhibit E. coli growth, among which the fraction < 3 kDa exhibited highest antimicrobial activity with a minimal inhibitory concentration of 30 mg/mL. Compared to other fractions, the fraction < 3 kDa contained higher content of hydrophobic amino acids (364.11 mg/g), in which about 79% of peptides had more than 60% hydrophobic ratio, potentially contributing to its antimicrobial activity. ICSE-keratinolysis process holds potential in reducing both protein resource waste and environmental pollution by valorizing feathers into antimicrobial product.